(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2025)
A study was conducted in the Charia area, Hathazari, Chattogram district, Bangladesh to determine the levels of carcinogenic metals Cd and Pb in soils and crop plants in the vicinity of brick kiln clusters. The health risk was evaluated by computing cancer risk using the US EPA model. The amounts of Cd and Pb in the soils and the parts of crop plants were determined by AAS. The soils of the study area were acidic. Metal concentrations indicating the anthropogenic input of Cd and Pd in the soils was in the range from 0.27 to 1.07 mg/kg dry soil and from 19.07 to 52.07 mg/kg dry soil respectively. Accumulation of Cd (0.00 to 0.27 mg/kg) and Pb (0.09 to 0.13 mg/kg) in the studied crops. A significantly high correlation (r = 0.89, p < 0.001) of the elements between soil and plant suggests that the source of contamination is the soil under study. 72% of all the studied edible plant parts exceeded the recommended threshold risk limit of the cumulative cancer risk (ƩILCR), which was higher in the edible part of fruit crops than in root crops. Cd was the dominant carcinogen in the study area. J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 17-31, June-December 2024